2018
DOI: 10.1111/rda.13158
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PSMD4 alters ZP1 ubiquitination state and sperm–oocyte‐binding ability in pigs

Abstract: The aim of this study was to determine how the duration of culture affects the ubiquitination of zona pellucida (ZP) proteins (ZP1, ZP2 and ZP3) during porcine oocyte maturation in vitro. We analysed the changes in ZP protein ubiquitination under three conditions: (i) during oocyte maturation from stage GV to MII; (ii) in oocytes cultured for different periods of time; and (iii) in oocytes treated with an antibody against PSMD4. Our results show that ZP1 and ZP2 are ubiquitinated at the GV stage, while ZP1, ZP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…It has been suggested that ZP1 might be ubiquitinated extracellularly during transport in the bloodstream to the IPVL [2,44], and/or when it passes through the gap between the GCs. Our immunohistochemical staining confirmed the presence of ubiquitinated proteins (identified in our study as ZP1), both in the IPVL as well as in the cytoplasm of the GC (especially the perinuclear cytoplasm), indicating the possibility of local ZP1 ubiquitination by GCs, as has been described for ZP proteins during pig oocyte maturation [47,48].…”
Section: Ubiquitinationsupporting
confidence: 88%
“…It has been suggested that ZP1 might be ubiquitinated extracellularly during transport in the bloodstream to the IPVL [2,44], and/or when it passes through the gap between the GCs. Our immunohistochemical staining confirmed the presence of ubiquitinated proteins (identified in our study as ZP1), both in the IPVL as well as in the cytoplasm of the GC (especially the perinuclear cytoplasm), indicating the possibility of local ZP1 ubiquitination by GCs, as has been described for ZP proteins during pig oocyte maturation [47,48].…”
Section: Ubiquitinationsupporting
confidence: 88%
“…SETDB1 plays an essential role in the maintenance of gonocyte survival in pigs, and knockdown of SETDB1 can induce gonocyte apoptosis [41]. PSMD4 effectively inhibits sperm-oocyte binding [42]. GNRHR2 is involved in regulating reproductive behaviour in pigs [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Akimov et al (2018) identified over 63,000 unique ubiquitination sites on 9,200 proteins in human cell lines by mass spectrometry. It is relevant to the regulation of the cell cycle, fertilization, oocyte maturation, and embryo development ( Xuan et al, 2018 ; Zhang Y. et al, 2018 ).…”
Section: Ubiquitination Regulates Oocyte Maturation and Embryo Developmentmentioning
confidence: 99%